Communicating with the martyrs’ families and their role in preserving the social structure Analytical study in the light of the Sunnah - المدرس اىٍصةغد ظةْر شٍس اىدَٗ ظةْر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Tha marty has a great position in Islam, because he sacrificed himself in order to preserve his homeland and his religion.Therefere, this study aimed to indentify the role of the prohet’s communication with the families of the margyrs in dealing with their psychological, social and economic effects, with how they integrate into society and build their own social. And all this through the analysis of the prophetic texts and the extraction of educational goala from them and their application in our contemporary reality.The researcher came to a group of results and the most important was the contact if the prophet with the mortyrs’ families which have an effective role in the treatment of psychological, social and economic effects with them to achieve justice by giving them their rights and at the same time return of the stolen from them. Baced on this, the researcher recommended several recommendations, the most important of is the continuous communication with the families of the martyrs to meet their needs thought securing their lives by and the disbursements of the money on their needs layment of debts of those families of martyrs